Pengembangan Multimedia Pembelajaran Interaktif Fisika Berbasis Macromedia Authorware 7.0 pada Materi Alat-Alat Optik dan Pemanasan Global Kelas XI SMA/MA - nurhasnah, nurhasnah; permaisuri, lili (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Research on multimedia interactive learning has been developed with various kinds of software and forms of instructional media such as material equipped with videos and quizzes. However, researchers developed interactive learning multimedia based on macromedia authorware 7.0 and media forms not only material, videos and quizzes, but also equipped with apperception, al-quran reading and Muslim scientists whose findings are in accordance with the material, namely optical devices and global warming. The purpose of this study is to produce physics-based interactive learning multimedia based on macromedia authorware 7.0 on material for optical devices and global warming class XI SMA / MA that are valid and practical. This research is research and development (research and development) using a 4-D model starting from defining, designing, developing and disseminating. The validity of interactive learning multimedia is measured in terms of the feasibility of content, media and language. Practicality is assessed from the ease of using interactive learning multimedia by educators and students of MAN XI IPA Pesisir Selatan class 2 . The instrument used in the validity and practicality test was a questionnaire with a Likert scale and analyzed by percentage techniques. The results showed that physics-based interactive learning multimedia based on macromedia authorware 7.0 on optical equipment and global warming material in class XI SMA / MA produced a valid and practical and effective interactive learning multimedia physics with very valid criteria (93.26%) and very practical criteria (88.23%).Â